Prevalence of HIV/syphilis co-infection among men who have sex with men in China: a systematic review and meta-analysis - Rong Su; Yi Liu; Duo Shan; Peilong Li; Lin Ge; Dongmin Li (BMC Public Health)
Abstract Background Men who have sex with men (MSM) are key populations for HIV and syphilis infection, and co-infection with both diseases significantly increases health risks. However, the co-infection of HIV/syphilis among this population in China has not been systematically evaluated. We aimed to conduct a meta-analysis to ascertain the prevalence of HIV/syphilis co-infection among MSM in China. Methods We conducted a systematic literature search involving PubMed, Web of Science, CNKI and Wanfang to identify publications reporting HIV/syphilis co-infection among MSM in China. Our search encompassed articles available from the establishment of these databases up to December 31, 2022. Additionally, we examined the references of retrieved articles to identify additional relevant records. The random-effects model fitting Freeman-Tukey double arcsine transformation was employed to estimate the prevalence of HIV/syphilis co-infection and its 95% confidence interval (CI). Heterogeneity was assessed utilizing the I 2 statistics and Cochran’s Q test. To explore the potential sources of heterogeneity, we conducted subgroup and meta-regression analyses. Results A total of 46 studies were included, with a total sample size of 50,187 MSM, including1,459 co-infected individuals. The pooled prevalence of HIV/syphilis co-infection among MSM in China was 2.7% (95% CI: 2.2-3.4%), with significant heterogeneity (I 2  = 90.5%, Q = 474.65, P < 0.01). Across China’s four regions, the Central region exhibited the highest co-infection prevalence (4.5%, 95% CI: 0.0-17.7%), followed by the Eastern region (3.1%, 95% CI: 2.4-3.9%) and Western region (2.4%, 95% CI: 1.8-3.1%). In contrast, the Northeast region reported the lowest co-infection prevalence (0.6%, 95% CI: 0.3-1.0%). Studies utilizing multiple sampling methods (4.7%, 95% CI: 3.6-6.0%) and recruiting MSM from sexually transmitted disease (STD) clinics (9.1%, 95% CI: 3.2-17.6%) showed higher prevalence of co-infection. Furthermore, the co-infection prevalence among MSM in China demonstrated a progressive increase with age. Conclusion The prevalence of HIV/syphilis co-infection among MSM in China was elevated, with certain regional disparities. Notably, the STD clinics attendees and older MSM were more likely to be co-infected. Urgent and targeted measures are needed to enhance interventions for these vulnerable populations to control HIV/syphilis co-infection.